Pauperland : poverty and the poor in Britain - Seabrook, Jeremy (Hurst, 2013)
In 1797 Jeremy Bentham prepared a map of poverty in Britain, which he called ""Pauperland."" More than two hundred years later, poverty and social deprivation remain widespread in Britain. Yet despite the investigations into poverty by Mayhew, Booth, and in the 20th century, Townsend, it remains largely unknown to, or often hidden from, those who are not poor. Pauperland is Jeremy Seabrook's account of the mutations of poverty over time, historical attitudes to the poor, and the lives of the impoverished themselves, from early Poor Laws till today. He explains how in the medieval world, wealth.